Proteomic and deep sequencing analysis of extracellular vesicles isolated from adult male and female Schistosoma japonicum. - Pengfei Du; Bikash R Giri; Juntao Liu; Tianqi Xia; Christoph G Grevelding; Guofeng Cheng (Public Library of Science (PLoS), 2020)
Schistosomes are the causative agent of schistosomiasis, which affects more than 200 million people worldwide. Unlike other trematode parasites, schistosomes (along with the Didymozoidae) have evolved separate sexes. Pairing of males and females is a prerequisite for female sexual development and subsequent egg production. However, the mechanisms underlying these processes remain poorly understood. Extracellular vesicles (EVs) have been shown to play important roles in many biological processes. In the present study, we characterized EVs isolated from adult male and female Schistosoma japonicum. Proteomic analyses of the isolated EVs revealed that some proteins are significantly enriched in male or female EVs. RNA-sequencing analysis of a small RNA population associated with EVs identified 18 miRNAs enriched in male and female S. japonicum EVs. Among these, miR-750 was specifically enriched in female EVs. Additionally, the inhibition of miR-750 by a miRNA inhibitor led to decreased egg production in female schistosomes cultured in vitro. Collectively, our results suggest that miR-750 within female EV cargo may be involved in regulating ovary development and egg production in S. japonicum females.